Radially symmetric shadow wave solutions to the system of pressureless gas dynamics in arbitrary dimensions. (November 2017) - Nedeljkov, Marko; Neumann, Lukas; Oberguggenberger, Michael; Sahoo, Manas R.
Abstract: Radially symmetric shadow wave solutions to the system of multidimensional pressureless gas dynamics are introduced, which allow one to capture concentration of mass. The transformation to a one-dimensional system with source terms is performed and physically meaningful boundary conditions at the origin are determined. Entropy conditions are derived and applied to single out physical (nonnegative mass) and dissipative (entropic) solutions. A complete solution to the pseudo-Riemann problem with initial data exhibiting a single delta shock on a sphere is obtained.